2022
DOI: 10.1007/s12603-022-1827-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Cognitive Problems as Determinants of Malnutrition in Long-Term Care Facilities, a Cross-Sectional and Prospective Study

Abstract: Objectives To investigate the cross-sectional and prospective associations between behavior and cognitive problems and malnutrition in long-term care facilities (LTCF). Design Cross-sectional and prospective routine care cohort study. Setting 6874 Residents in Dutch LTCFs (period 2005–2020). Participants Data were obtained from the InterRAI-LTCF instrument. Cross-sectional an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…For this research we used cross-sectional as well as prospective data obtained from the Dutch InterRAI database for Long-Term Care Facilities (InterRAI LTCF). These data have been previously described by our group [236].…”
Section: Data Sourcesupporting
confidence: 78%
See 3 more Smart Citations
“…For this research we used cross-sectional as well as prospective data obtained from the Dutch InterRAI database for Long-Term Care Facilities (InterRAI LTCF). These data have been previously described by our group [236].…”
Section: Data Sourcesupporting
confidence: 78%
“…In contrast, neuropsychological problems, which are widely accepted as a risk factor for developing malnutrition [66], were not associated with lower intakes in our study. A previous study by our group showed that especially residents with multiple cognitive problems are at increased risk of developing malnutrition [236]. As we had only limited data on neuropsychological problems, we were not able to test the relation of multiple cognitive problems on protein and energy intake.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…For this research, we used cross-sectional, as well as prospective, data obtained from the Dutch InterRAI database for Long-Term Care Facilities (InterRAI LTCF). These data have been previously described by our group [ 20 ].…”
Section: Methodsmentioning
confidence: 73%